Relationship between SME financing and livelihood standard: evidence from Bangladesh / Shakhawat Hossain Sarkar and Sumaiya Aktar - Sarkar, Shakhawat Hossain; Aktar, Sumaiya (Universiti Teknologi MARA, Cawangan Melaka, 2023)
Small and medium enterprises (SMEs) play significant roles in individuals' socioeconomic development vis-à-vis a country's national development. The study aimed to evaluate the relationship between SME financing and the development of livelihood standards in Bangladesh. Primary sources of data were collected from the respondents by administering a semi-structured questionnaire at different Upazila under the Mymensingh district. The dichotomous variable was applied to determine the relationship where a score of '1' was assigned if the item complied and '0' otherwise. Frequency, percentile, likelihood-ratio chisquare, Fisher's exact test, and paired sample test were used to get the result. The likelihood-ratio value specifies a significant relationship between the development of livelihood standards and the length of business at 5 per cent and the development of livelihood standards and SME finance at a 6.4 per cent level of significance. Sex, education level, training on SME of the respondents, ownership type, the share of the loan, and business nature has an insignificant relationship with the development of livelihood standard. Paired samples test indicates a positive relationship between livelihood development stimuli (LDS) and the development of livelihood standards. The study will enrich the literature on SME financing and the socioeconomic development of individuals and a country. The findings of the study will be helpful for the policy-making and implementation-level authorities to make suitable policies regarding SME financing. There is a generalisation limitation because the study only covered one district out of sixty-four districts in Bangladesh. Future research should overcome the limitation.